ANALISIS DAMPAK DARI SOCIAL PRESENCE, INTERACTIVITY, ATTRACTIVENESS DAN EXPERTISE PADA FLOW TERHADAP PURCHASE INTENTION DAN CONTINOUS WATCHING INTENTION LIVE STREAMING TIKTOK SHOP - Lutfia, Nurul; Wulandari , Nuri (Journal of Accounting, Management and Islamic Economics, 2025)
The background to this research is based on the importance of customer orientation in increasing customer satisfaction in the banking sector, especially at Bank Mandiri Jakarta Condet Branch. In intense competition, banks must be responsive to customer needs and provide quality services to maintain customer satisfaction and loyalty. Previous research shows a relationship between customer orientation and customer satisfaction, but the role of service quality as a mediator has not been thoroughly explored. This research aims to examine the influence of customer orientation on customer satisfaction which is mediated by service quality. The research method used is a quantitative approach with a descriptive design. Data was collected by distributing questionnaires to 100 customers of Bank Mandiri Jakarta Condet Branch. The analysis technique used is Partial Least Squares (PLS) to test hypotheses and research models. The research results show that consumer orientation has a significant positive influence on consumer satisfaction. Apart from that, service quality is also proven to mediate the relationship between customer orientation and customer satisfaction. Data analysis shows that service quality plays an important role in strengthening the influence of customer orientation on customer satisfaction. This indicates that banks that are able to provide quality services, in accordance with their customers' needs, will be able to increase customer satisfaction significantly. The conclusion of this research is that service quality is an important factor that strengthens the relationship between customer orientation and customer satisfaction.